The Role of Algorithms and the Formation of Hate Speech Polarization on Twitter (Case Study of Video Content of KH Said Aqil Siradj's Visit after the Suicide Bomb Explosion at Makassar Cathedral) - Fidelis Aggiornamento Saintio (Jurnal Nomosleca, 2023)
After the 2021 suicide bombing at the Makassar Cathedral church, the general chairman of PBNU, Said Aqil Siradj, visited the Makassar Cathedral to provide moral support to Catholics. The video of thevisit provoked reactions both in the digital realm and offline. Even though this visit had a positive nuance, on Twitter there were comments containing insults and hate speech. This research uses qualitative text analysis to analyze the comments that appear andanswer why video content that has a positive nuance and contains tolerance can trigger negative comments. The results of this research prove that polarized comments are not much influenced by the content. The content becomes a trigger so that like-minded people can confirm the beliefs they have long held. Apart from that, from this study, researchers see that there are things outside humans (non-humans) that shape the interpretation of social media users. This network of people with the same beliefs is united by features of social media platforms that bring users closer together,namely comments, retweets and likes.